2021
DOI: 10.1038/s41467-021-22209-w
|View full text |Cite
|
Sign up to set email alerts
|

Sub-diffractional cavity modes of terahertz hyperbolic phonon polaritons in tin oxide

Abstract: Hyperbolic phonon polaritons have recently attracted considerable attention in nanophotonics mostly due to their intrinsic strong electromagnetic field confinement, ultraslow polariton group velocities, and long lifetimes. Here we introduce tin oxide (SnO2) nanobelts as a photonic platform for the transport of surface and volume phonon polaritons in the mid- to far-infrared frequency range. This report brings a comprehensive description of the polaritonic properties of SnO2 as a nanometer-sized dielectric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…In particular, GST326 was shown to switch reversibly between amorphous and crystalline states when investigated with mid-infrared SNOM 21 and the related compound GST124 was shown to possess far-infrared SNOM contrast between the crystalline and amorphous states. 58 In this work, SNOM is used with illumination from a CO 2 laser and the infrared-to-THz free-electron laser (FEL) FELBE in Dresden, Germany, 57,59,63,71,80 to investigate the nanoscale optical properties and free charge carriers of GST326 in the mid-and far-infrared range, i.e., at 885 cm −1 (11.3 μm, 26.5 THz) and 168 cm −1 (59.5 μm, 5.04 THz), respectively, complemented by simultaneous KPFM measurements (cf. the Supporting Information for experimental details).…”
Section: Nano Lettersmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, GST326 was shown to switch reversibly between amorphous and crystalline states when investigated with mid-infrared SNOM 21 and the related compound GST124 was shown to possess far-infrared SNOM contrast between the crystalline and amorphous states. 58 In this work, SNOM is used with illumination from a CO 2 laser and the infrared-to-THz free-electron laser (FEL) FELBE in Dresden, Germany, 57,59,63,71,80 to investigate the nanoscale optical properties and free charge carriers of GST326 in the mid-and far-infrared range, i.e., at 885 cm −1 (11.3 μm, 26.5 THz) and 168 cm −1 (59.5 μm, 5.04 THz), respectively, complemented by simultaneous KPFM measurements (cf. the Supporting Information for experimental details).…”
Section: Nano Lettersmentioning
confidence: 99%
“…Scattering-type scanning near-field optical microscopy (SNOM, Figure c) fulfills these criteria by using strongly confined optical near-fields at the apex of a sharp metallic tip to probe nanoscale areas of the sample. , These near-fields extend beyond the immediate surface, typically penetrating up to 100 nm into the sample, and thus provide additional subsurface information. Optical frequencies in the infrared range can be used to investigate characteristic phonon resonances and free charge carriers, giving insight into local electronic and structural properties with nanoscale resolution. For plasmons of low charge carrier density or phonons of heavy atoms, near-field contrast is typically found at low energies, requiring SNOM at far-infrared frequencies. ,, The spectral region of 33–334 cm –1 (1–10 THz, 30–300 μm) is difficult to access experimentally and is therefore often referred to as the “THz gap” . Despite these challenges, SNOM at THz frequencies has recently become a vibrant field of research, providing fundamental insight into low-energy and high-momentum excitations, such as nonlocal effects in single-layer graphene, subwavelength metal structures, , and phonon polaritons. , Similar to SNOM, Kelvin probe force microscopy (KPFM) possesses the high resolution of several nanometers typical for atomic force microscopy (AFM) techniques. However, KPFM measures the local surface potential instead of the optical properties.…”
mentioning
confidence: 99%
“…In this work, we exploit the polaritonic response of α-MoO 3 nanobelts, with reduced dimensionality approaching “1D-like” (Figure c), using synchrotron infrared nanospectroscopy (SINS) and scattering-scanning near-field optical microscopy (s-SNOM). As reported, such nanoscopy techniques (see details in Supporting Information) possess a high spatial resolution and momentum nanoprobe allowing for full characterization of HP 2 waves.…”
mentioning
confidence: 99%
“…It is found that the absorption strength of AP 2 in all the proposed MSA achieved the maximum value when the thickness reached S H = 50 nm. It can be explained by the fact that AP 2 is excited by the cavity modes ( [26,27])b e t w e e nt h e layers of upper grating and the tungsten lower plate. The insets in Figure 2 show the excitation of the cavity modes at λ = 1455 nm for tungsten, at λ = 1200 nm for rhenium, at λ = 1260 nm for tantalum, and at λ = 1245 nm for molybdenum.…”
Section: Underlying Mechanisms For High Broadband Solar Absorptionmentioning
confidence: 99%